Accelerated Fibrinolysis and Its Propagation on Vascular Endothelial Cells by Secreted and Retained tPA. (12th October 2012) - Urano, Tetsumei; Suzuki, Yuko
Abstract : We successfully visualized the secretory dynamics of tissue-type plasminogen activator (tPA) tagged by green fluorescent protein (tPA-GFP) from cultured vascular endothelial cells (VECs) using total internal reflection fluorescence (TIRF) microscopy and demonstrated that tPA-GFP secreted from VECs was retained on cell surfaces in a heavy-chain-dependent manner. Progressive binding of Alexa568-labeled Glu-plasminogen was also observed on the surface of active tPA-GFP expressing cells via lysine binding sites (LBS), which was not observed on inactive mutant tPA-GFP expressing cells. These results suggest that retained tPA on VECs effectively activated plasminogen to plasmin, which then facilitated the binding of additional plasminogen on the cell surface by proteolytically cleaving surface-associated proteins and exposing their C-terminal lysine residues. Thus prolonged retention of tPA appeared to play an important role in initiating and amplifying plasmin generation on VECs. LBS-dependent binding of plasminogen was also observed as a narrow band at the lytic front of the fibrin mesh formed on active tPA-GFP expressing cells, which expanded outward as the lytic area increased. This binding was not observed on inactive mutant tPA-GFP expressing cells or in the presence of aprotinin. The binding of plasminogen to partially digested fibrin appears to be indispensable for spontaneous fibrinolysis.